Comparative Study of Temperature and Rainfall Fluctuation in Hunza-Nagar District - Sheeba Afsar; Nasir Abbas; Bulbul Jan (Journal of Basic & Applied Sciences, 2013)
Climate assessment essentially involves a good understanding of rainfall and temperature patterns. As such, there are many factors to be considered while studying climate. Although, temperature and rainfall are playing an extremely important and manifold role in climatic research particularly in various environmental hazards. The aim of this study was to develop and validate a forecasting model that could predict temperature and rainfall and provide timely early warning in Hunza-Nagar. In this paper temperature and rainfall dataset (2007-2011) have used and developed a quantitative treatment using different statistical methods such as regression and time series/stochastic modeling. The regression analysis proposes that the rainfall increased with increasing temperature. It also found that trends in monthly mean maximum temperature indices increase from years 2007 to 2011 while the amount of rainfall has decreased. The available data presented that AR (1) model is most adequate for a forecast of temperature. These forecasts will be useful for public, private and government organization.